Arash Abazari, Hegel's Ontology of Power. The Structure of Social Domination in Capitalism, Cambridge University Press, Cambridge, 218pp. ISBN: 978-1-108-83486-5 - Aguiriano Benéitez, Mario (Antítesis - Revista iberoamericana de estudios hegelianos, 2021)
Reseña del libro de Arash Abazari: Hegel's Ontology of Power. The Structure of Social Domination in Capitalism, Cambridge University Press, Cambridge, 218pp. ISBN: 978-1-108-83486-5.